La alimentación en la corte española del siglo XVIII - Pérez Samper, María de los Ángeles (Cuadernos de Historia Moderna, 2003)
The court is a complex world, but it is also complicate when we talk about its nourishment. The study of the real table allows to observe the identification and the contrast between the person and the institution, because it serves so much to the satisfaction as the vital necessities of the monarch, like to the satisfaction of the institutional necessities, reason why it will be always an plentiful table, refined, splendid, manifestation of the power and the prestige of the Spanish Monarchy. The nourishment to the 18th century court was characterized by the introduction of a different and new taste. From the accession to the throne of Felipe V, it prevailed the French kitchen, derived from the French origin of the dynasty, the presence of French cooks in the Court and the prestige of the French gastronomy. The first Borbón, in the same way that changed other things of the Spanish Monarchy and how he governed the artistic style, changed as well how to eat.